Study on segment routing network and its application in traffic engineering - Xiaoming HE; Quan LU; Liang XING (Dianxin kexue, 2016)
Segment routing network is the inheritance and innovation of IP routing technology，which has many unique advantages in the realization of network virtualization，fast re-routing，network programming，load balancing and traffic engineering，and so on.Segment routing mechanism was studied in depth，and the protocol extensions of interior gateway protocols （IGP）and border gateway protocol （BGP）for segment routing were introduced and analyzed in detail.Furthermore，the realization of traffic engineering for segment routing in typical application scenarios of the operator networks was explored.With the maturity of technology and standardization，segment routing network will promise to have broad application prospects.